HAMBATAN PENGAMBILAN KEPUTUSAN DALAM BERWIRAUSAHA BAGI PEREMPUAN DALAM ORGANISASI PEREMPUAN - Faizal Ahmad (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The contribution of women in the progress of entrepreneurship is gaining attention. Based on the data from the Ministry of Cooperative and Small Medium Enterprises (SMEs) shows that women dominate SMEs in Indonesia. It is undoubtedly a positive sign for women's empowerment and its impact on the national economy. However, the influence of culture on the role of women in the world of entrepreneurship needs to be taken seriously. It can be seen from the considerable number of inhibiting factors in the development of women's entrepreneurship. In order to overcome this condition, it is interesting to examine women's active role in the organization as part of the solution. However, even though it is within the scope of the organization, the inhibiting factors for entrepreneurial decisions are still seriously challenging, especially in the aspects of social and interpersonal pressure experienced by women in preparing entrepreneurial decisions. This research will identify factors that prevent women from making entrepreneurial decisions, especially women in women's organization.